Factors for Rituximab Refractoriness in AQP4‐IgG+ NMOSD: A Cohort Study - Mariano Marrodan; María A. Piedrabuena; María A. Zarate; Sofía Rodríguez Murúa; Ezequiel I. Surace; Mauricio F. Farez; Marcela P. Fiol; María C. Ysrraelit; Jorge Correale (Annals of Clinical and Translational Neurology)
ABSTRACT Objective Neuromyelitis optica spectrum disorder (NMOSD) is a severe autoimmune condition of the central nervous system (CNS), often associated with aquaporin‐4 antibodies (AQP4‐IgG). Rituximab, a CD20+ B‐cell depleting monoclonal antibody, is widely used as first‐line therapy. However, a subset of patients exhibits treatment refractoriness. Our objective is to investigate factors associated with treatment refractoriness in AQP4‐IgG‐positive NMOSD patients treated with rituximab. Methods This retrospective cohort study included 54 AQP4‐IgG‐positive NMOSD patients treated with rituximab between 2006 and 2023. Clinical, imaging, and genetic data were analyzed. Treatment failure was defined as at least one relapse occurring after 6 months of rituximab initiation. Statistical analyses included multivariate analyses of covariance (MANCOVA) and Cox regression to identify independent predictors of treatment failure. Results Among the 54 patients (82.5% female, median age 45 years, range: 34–54.5), 12 (22.2%) exhibited rituximab treatment failure. The presence of asymptomatic lesions during follow‐up was significantly associated with treatment failure (p = 0.02) and emerged as an independent predictor in MANCOVA (Wilks' Lambda = 0.01, F = 20.5, η2 = 0.357, p < 0.001). These lesions also increased the risk of clinical relapses (HR = 25.9, 95% CI = 3.09–218, p < 0.01). Other variables, including age, sex, baseline EDSS, and persistent gadolinium enhancement, were not significantly associated with treatment failure. Genetic analysis of the FCGR3A‐V158F polymorphism did not reveal a significant relationship with treatment outcomes. Interpretation Asymptomatic lesions during rituximab treatment are a strong predictor of therapeutic failure in AQP4‐IgG‐positive NMOSD patients. Early identification of these lesions could guide clinicians in optimizing treatment strategies, including transitioning to alternative therapies.